Seed priming-induced enhancement in seed germination, Seedling vigor, and productivity of foxtail millet (Setaria italica L.) in winter and summer seasons under Bangladesh conditions - A. K. M. Mominul Islam; Tamanna Khatun; Prianka Chanda Bipra; Md. Sazzad; Tapon Kumar Roy; Md. Masud Rana; Sabina Yeasmin; Sinthia Afsana Kheya; Sanjida Afrin Urmi; Mst. Masuma Momtaj Meem; Md. Parvez Anwar; A. K. M. Aminul Islam (PLoS ONE, 2026)
Foxtail millet is a nutritionally rich and climate-resilient cereal crop; however, poor germination and weak early seedling growth often limit its productivity. This study evaluated the effects of seed priming on germination, seedling vigor, yield attributes, and grain yield of foxtail millet through laboratory and field experiments. In the laboratory study, four foxtail millet varieties were subjected to six priming chemicals at two concentrations each, along with hydropriming and an unprimed control. Seed priming significantly influenced all germination and seedling vigor traits. The highest germination percentage (86.44%) and germination index (116.49), were recorded under NaCl priming at 10000 ppm. Maximum seedling vigor index (6.08), speed of emergence (86.51), germination energy (61.63) were achieved with NaOCl at 500 ppm, while the lowest germination performance occurred under CaCl 2 at 20000 ppm. The shortest time to 50% germination (T 50 = 1.55 days), mean germination time (MGT = 4.54 days) and seedling vigor index were obtained from no priming, while the longest T 50 (2.0 days) and MGT (4.78 days) were recorded with KNO 3 at 30000 ppm. The longest shoot (3.76 cm) and shoot dry weight (28.96 mg) were obtained with KNO 3 at 15000 ppm, while the longest root (3.92 cm) and seedling length (7.51 cm) were recorded under NaOCl at 1000 ppm. The lowest shoot length (2.18 cm), root length (2.08 cm), seedling length (4.26 cm), shoot (12.03 mg), root (10.66 mg) and seedling (22.69 mg) dry weight were obtained from no priming. Based on laboratory performance, selected treatments were evaluated under field conditions. During the winter season, the highest grain (2.72 t ha -1 ) and straw (5.03 t ha -1 ) were recorded from BARI Kaon-2 × NaCl (10000 ppm). The highest grain yield obtained under this treatment combination was due to the production of the highest values for ear length (17.83 cm), ear weight (14.30 g), filled grains ear -1 (2918.33) and 1000-grain weight (2.56 g). Whereas, the lowest grain yield (1.17 t ha -1 ) was given by BARI Kaon-1 × no priming. In the summer season, the highest grain yield (3.93 t ha -1 ) was obtained from BARI Kaon-1 × NaCl (10000 ppm) this was due to the production of the higher values for most of the yield attributes by this treatment combination. In summer season, the lowest grain yield was obtained from BARI Kaon-4 × no priming. In conclusion, BARI Kaon-2 × NaCl (10000 ppm) performed best during the winter season, whereas BARI Kaon-1 × NaCl (10000 ppm) exhibited superior performance during the summer season. Seed priming with NaCl (10000 ppm) emerged as a seasonally robust strategy to improve germination, crop establishment, and yield of foxtail millet in Bangladesh.